Effect of Dietary Supplementation of Giloy (Tinospora cordifolia) Herb and Ascorbic Acid Along with Different Bedding Materials on Cost Economics of Japanese Quail Rearing - Poonia, Narender Kumar; Choudhary, Garima; Kumar, V. (International Journal of Bio-resource and Stress Management, 2023)
The present studywas conducted during October, 2020 to April, 2021 at the Poultry unit, Livestock Farm Complex, College of Veterinary and Animal Science, Bikaner, Rajasthan University of Veterinary and Animal Sciences, Bikaner, Rajasthan, India to investigate the effects of Giloy and ascorbic acid supplementation along with different bedding materials (sand, saw dust and wheat straw) on cost economics of Japanese quails rearing for 24 weeks .Four hundred thirty two (432) laying Japanese quails (7 day old) were divided into three of different bedding material and each bedding material group further subdivided into four groups on the basis of supplementation (control, Giloy, ascorbic acid and combination of both). Thus, birds were randomly and uniformly distributed in total 12 treatment groups comprising of 36 birds in each group and each group further divided into two replicates comprising 18 birds in each replicate. Quails were fed a basal diet and the basal diet supplemented with 5 g kg-1 giloy supplement of diet, 240 mg of ascorbic acid kg-1 supplement of diet and a combination of 5 g kg-1 giloy and 240 mg of ascorbic acid kg-1 supplement of diet. The net profit/bird based on overall interaction effect was found highest in the group supplemented with giloy alone and reared on wheat straw as bedding material followed by saw dust and sand bedding material group, which were supplemented with giloy alone, respectively. The present study shows that dietary supplementation of giloyalong with wheat straw bedding material is beneficial for cost economics.